2016
DOI: 10.3389/fphar.2016.00238
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Polymorphisms Associated to Folate Transport as Predictors of Increased Risk for Acute Lymphoblastic Leukemia in Mexican Children

Abstract: Acute lymphoblastic leukemia (ALL) is a frequent neoplasia occurring in children. The most commonly used drug for the treatment of ALL is methotrexate (MTX), an anti-folate agent. Previous studies suggest that folate transporters play a role in ALL prognosis and that genetic polymorphism of genes encoding folate transporters may increase the risk of ALL. Therefore, the main goal of this study was to determine the associations among six genetic polymorphisms in four genes related with the folate transporter pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
5
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 44 publications
0
5
0
Order By: Relevance
“…Kunická T. and Souček P., ( Kunická and Souček 2014 ) mentioned that resistance to multiple drugs has one of the most important causes of cancer treatment failure, ABC transporters are membrane-bound proteins that participate in cell defense mechanisms, hence their function is to prevent toxicity as carcinogenesis on the one hand, but may contribute to resistance of tumor cells to a number of drugs, including chemotherapeutics. Zaruma-Torres F et al ( Zaruma-Torres et al, 2016 ) in 2016 found that the ABCB1 rs1045642 and ABCC5 rs3792585 polymorphisms were associated with an increased risk of ALL in Mexican children. In the current study, we determinate the impact of three gene polymorphisms involved in the metabolism of antineoplastic drugs, such as the NCF4 rs1883112, CBR 3 rs1056892 and ABCC1 rs3743527 polymorphisms, we also provided frequencies of this variants and identify any association with the development of ALL in children.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Kunická T. and Souček P., ( Kunická and Souček 2014 ) mentioned that resistance to multiple drugs has one of the most important causes of cancer treatment failure, ABC transporters are membrane-bound proteins that participate in cell defense mechanisms, hence their function is to prevent toxicity as carcinogenesis on the one hand, but may contribute to resistance of tumor cells to a number of drugs, including chemotherapeutics. Zaruma-Torres F et al ( Zaruma-Torres et al, 2016 ) in 2016 found that the ABCB1 rs1045642 and ABCC5 rs3792585 polymorphisms were associated with an increased risk of ALL in Mexican children. In the current study, we determinate the impact of three gene polymorphisms involved in the metabolism of antineoplastic drugs, such as the NCF4 rs1883112, CBR 3 rs1056892 and ABCC1 rs3743527 polymorphisms, we also provided frequencies of this variants and identify any association with the development of ALL in children.…”
Section: Discussionmentioning
confidence: 99%
“…Kunická T. and Souček P., (Kunická and Souček 2014) mentioned that resistance to multiple drugs has one of the most important causes of cancer treatment failure, ABC transporters are membrane-bound proteins that participate in cell defense mechanisms, hence their function is to prevent toxicity as carcinogenesis on the one hand, but may contribute to resistance of tumor cells to a number of drugs, including chemotherapeutics. Zaruma-Torres F et al (Zaruma-Torres et al, 2016) in 2016 found that the ABCB1 rs1045642 and ABCC5 rs3792585 polymorphisms were associated with an increased risk of ALL in Mexican children.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Mutations in the CYP1A1 and GSTM1 genes were relevant in oral cancer in Latin Americans [149], also detected in Asians [150,151,152]. The hRAD54 , hMSH2 , ABCB1 , ABCC5 , COL18A1 , and SLC19A1 genes were consistent with lymphoma and leukemia in Latin Americans [153,154,155,156], as well as some Caucasians and Asians [157,158,159,160]. The RB1 gene was related with retinoblastoma in Latin Americans [161,162], and the TNFα and TP53 genes with cervical cancer [163,164,165,166,167,168].…”
Section: Germline Cancer Predisposition In Latin Americamentioning
confidence: 99%
“…The lower left quadrant of Figure 5 has themes of low centrality and density that can represent emerging or disappearing themes. Within the theme “leukemia” we found the high occurrence concepts like “lymphoblastic”, which implies that it could be an emergent theme of specialization in the study of leukemia currently known as one of the biggest health problems in Mexican children [ 44 , 45 ]. Another theme that stands out is “networks”, where high occurrence concepts, such as “regulatory”, “coli” suggests that this theme has been influenced by one of the pioneering topics (gene regulation) of Mexican bioinformatics led by Dr. Collado-Vides and additional terms like “system”, “model” suggest an integrative stage of the theme for the study of gene regulation.…”
Section: Discussionmentioning
confidence: 99%